Waving potential at volt level by a pair of graphene sheets. (June 2019) - Fei, Wenwen; Shen, Chun; Zhang, Shiyu; Chen, Hongye; Li, Luxian; Guo, Wanlin
Abstract: Electricity generated from liquid flow on graphene has triggered great interests and shown its prospect in harvesting mechanical water energy. However, most attention so far has just been paid to voltage induced in graphene, little is paid for the energy induced by ions movement on liquid side. Here, by employing a pair of graphene sheets, we report the electricity generation in liquid. An open circuit voltage up to 1 V can be obtained as graphene moves across electrolyte solution. Molecular dynamics simulations indicate that the underlying mechanism is due to potential difference generated between solutions near graphene surface and that in the bulk. Experimental results show that the generated voltage has a close relation with moving speed of graphene, ion concentration and species. This work of considering ion motion in solution should provide new ideas for the development in harvesting water energy with graphene. Graphical abstract: Image 1 Highlights: Employing a pair of graphene sheets generates waving potential at volt level. Such waving potential can be utilized as power supply for external circuit. Deep insight of underlying mechanism is given by comprehensive experiments and molecular dynamic simulations.